Gestión de Riesgos Laborales en la Empresa Textiles La Escala-ECUALGODÓN S.A - Córdova, Juan (2012)
At the present time the globalization of the economy is a world tendency that studies with the liberalization of commerce and the economic integration. New technological risks and of organization of the work they will be the challenges for the process of which we are part. Because in the Ecuador, it is an indispensable requirement that in each working center it possesses a Bylaw that you/they fulfill the requirements as regards Security and working Health, and that whose content is framed in national, international and community norms. It is of waiting that outlined this way, each Bylaw is particular and specific for each working center, the same as they are it its risks, because, like it is the case of the plants of Textiles La Escala y Textiles La Escala-Ecualgodón S.A., although the productive activity, the machinery, tool, facilities, processes, raw material, auxiliary and products were similar, I didn't seize the organization of the work, the distribution of tasks, the days and the most important thing the motivation state, satisfaction and level of commitment of its human capital that it impacts directly in the productivity. For this reason, this paper aims not only to solve a requirement, but the conditions and labor relations from being captured, and therefore it is important that has a regulation that meets and complies with the requirements of every business in Ecuador. With the elaboration of the regulation he/she seeks to improve the labor atmosphere, the working conditions, to minimize the potential risks and accidents to those that are exposed, the level of productivity and mainly fulfilling a requirement that all company needs for its correct, appropriate and sure operation legally.